The Leading-Edge Detection of Caffeine by a Green Electrode. - Đỗ, Mai Nguyễn; Trần, Quang Huy (Tạp chí Khoa học Đại học Đông Á, 2024)
The RSCD-modified electrode has excellent catalytic electrochemistry properties to CFE with a well-defined electrochemical peak, at 1.26 V. The linear correlation of the peak current, Ip of CFE and the concentration range (0.2 µM – 1.4 µM) give a small LOD value of 0.095 M and LOQ value of 0.313 M. This illustrates good sensitivity and the ability to apply the modified electrode to detect CFE in several practical matrix samples.